DISPARITAS KOMPETENSI ALUMNI PENDIDIKAN BISNIS FE UNIMED: ANALISIS KESENJANGAN MENUJU KESIAPAN ADAPTASI DI ERA INDUSTRI 5.0 - Baskoro, Danny Ajar; Hasibuan, Novita Indah; Sihombing, Rossy Pratiwiy; Handriyani, Richna (STKIP Pesisir Selatan, 2025)
The rapid dynamics of the industrial revolution, particularly in the Industry 5.0 era, demand that university graduates possess high adaptive and relevant competencies. This study identifies and thoroughly analyzes the disparity in competencies between the knowledge gained during higher education and the demands of the professional world among alumni of the Business Education Study Program, Faculty of Economics, Universitas Negeri Medan (FE Unimed). Employing a quantitative descriptive-analytic approach, data was collected through questionnaires from 127 alumni who graduated between 2021 and 2024. The research results explicitly indicate varying competency gaps. The most significant gap was found in Entrepreneurship and Innovation (gap = 1.02). Furthermore, gaps were also identified in Pedagogical Competence (gap = 0.09), Adaptation and Problem Solving (gap = 0.09), and Managerial Competence (gap = 0.08), all of which are categorized as high priority for improvement. Meanwhile, Information Technology Skills (gap = 0.09) and Communication and Collaboration (gap = 0.09) showed moderate gaps, and Professional Ethics (gap = 0.05) demonstrated the lowest gap. These findings underscore the urgency for curriculum adjustment, strengthening of practice-based learning methods, and increased strategic collaboration with industry stakeholders. The implementation of these recommendations is crucial to ensure that FE Unimed graduates possess relevant competencies and are capable of proactively adapting to the challenges and opportunities presented by the Industry 5.0 era.